Efficacy and safety of robot-assisted versus endo-laparoscopic ventral hernia repair: a meta-analysis of randomized controlled trials - Junfeng Li; Shihong Li; Lunwu Wei; Huiping Li (BMC Surgery)
Abstract Purpose To comprehensively compare the surgical outcomes of robotic ventral hernia repair (rVHR) with traditional endo-laparoscopic ventral hernia repair (lapVHR) using systematic review methods, evaluating the efficacy and safety of rVHR and providing reference for clinical applications of rVHR. Methods This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) list. The following electronic databases were searched: PubMed, Web of science, Cochrane library, Embase, Scopus, and SpringerLink. The retrieval period spanned from the inception of database until 2024. Only randomized controlled trials were included. Outcomes of recurrence, re-hernioplasty, operative time, length of hospital stay and surgical site occurrence were compared between rVHR and lapVHR. Results A total of 5 studies (237 patients) were included in the meta-analysis. Compared with lapVHR, the treatment of rVHR significantly decreased re-hernioplasty (RR = 0.17, 95% CI 0.04–0.66). Additionally, rVHR significantly reduced the length of hospital stay (MD = 0.48, 95% CI: 0.25, 0.71) and operative time (MD = 69.45, 95%CI: 45.76, 93.14). In addition, rVHR can reduce the recurrence rate, but it is a marginal statistical difference (RR = 0.46, 95% CI: 0.19, 1.13). Conclusion Overall, both rVHR and lapVHR were effective and safe. Nevertheless, rVHR shows superiority in terms of recurrence rate and re-hernioplasty rate. More high-quality studies are warranted to validate the results of this study.